Medical students participation on KKN program (community service learning): Improving community health through health promotion - Hasna Fikriya; Herdifitrianne Saintissa Yanuaristi; Helen Natalia (BKM Public Health and Community Medicine, 2021)
Objective: This study aims to describe the medical students' involvement in KKN Program (community service learning) to improve community health through health promotions. Content: KKN Program is a multidisciplinary research-based community service program to enhance, empower, and enable society to increase control over, and improve, their lives including health. Among community health improvement approaches, KKN Program heavily highlights health promotion. In line with ‘organized effort’ as the core definition of public health by WHO, KKN Program requires collaboration between multidisciplinary students, the community (partners and government), and the university. As a type of experiential learning, KKN Program allows medical students to apply their knowledge and skills in relevant community-based contexts. Students learn to develop critical thinking skills, explore ethical and social justice concerns, and reflect according to their perspectives. KKN Program provides a platform to implement health promotion interventions to boost health outcomes. Numerous examples of health intervention in the KKN program include building health policy, generating a health-promoting environment, community action, helping health care services, and developing personal skills. A range of actions in KKN programs such as community visits, campaigns, facilitated counseling & support, and assistance of current primary health care programs are essential for students to obtain public health skills comprising analytical/assessment skills, program planning skills, communication skills, and management and evaluative reasoning skills. In conclusion, the KKN program provides common ground for medical students to equally learn first-hand from the community and assist their role to become 5-star physicians: care-provider, decision-maker, communicator, community leader, and manager. It equips medical students as future general practitioners with public health skills and the mindset required to improve community health.